The Song “The Girl from Ipanema” and Bossa Nova Music by Antonio Carlos Jobim - Lawongsa, Rapeepol (Journal of Fine and Applied Arts Khon Kaen University, 2024)
The purpose of this article is to explore the history and origins of the Bossa Nova music genre, which was heavily influenced by the musical styles of Cool Jazz and Samba and was often referred to as the "New Wave" of Brazilian music. In addition, it aims to narrate the history of Antonio Carlos Jobim, the legendary bossa nova guitarist, and his collaboration with the white Brazilian musician Joao Gilberto. Together, they created the distinctive Bossa Nova music style on the iconic Ipanema beach in Brazil. The genre achieved worldwide recognition with the timeless classic, "The Girl from Ipanema." Furthermore, this article provides an analysis of the musical characteristics found in "The Girl from Ipanema." The song incorporates various techniques from the Cool Jazz genre, including the use of seventh chords, reharmonization, secondary dominants, tritone substitution, and half-step bassline variations. This blending of musical elements aligns with the description of Bossa Nova as often being referred to as "Brazilian Jazz."